LAMPUNG SELATAN LOCAL WISDOM BERBASIS BUKU PINTAR DIGITAL SEBAGAI INOVASI PEMBELAJARAN IPA DIMASA POST PANDEMIK - haka, nukhbatul (Universitas Islam Jember, 2022)
The teaching materials that are currently used by most educators are still very general with material descriptions that are more dominant in text than images that can help students understand lessons, besides that the use of technology in education is still not optimized in learning. This study aims to determine the feasibility of teaching material products in learning. This research is a type of research and development (R&D) with a 7-step Borg and Gall model development procedure. These teaching materials were validated by media experts, material experts, and Indonesian language experts. The validation of media experts obtained a score of 89%, material experts 92%, and Indonesian language experts 94%. The product trial with 30 respondents got a percentage value of 91% and an assessment from the teacher of 93%. Based on the results of the study, it can be concluded that digital smartbooks with local wisdom developed are very feasible to be implemented as material.